Spatial analysis and urban land use planning emphasising hospital site selection: a case study of Isfahan city - Soltani Ali; Inaloo Rasoul Balaghi; Rezaei Mohammad; Shaer Fatemeh; Riyabi M. Akbari (Bulletin of Geography. Socio-Economic Series, 2019)
Providing appropriate and equal healthcare to the various classes of society is among the major issues in social welfare. The spatial distribution and locating of health service centres are significant in addressing the healthcare needs of citizens. This issue needs to be evaluated using quantitative and qualitative approaches throughout those cities with high populations and activity density levels. By taking Isfahan metropolitan area as the case study area, in this study, a combination of Network Analyst tool within Geographic Information System (GIS) and an Analytic Hierarchy Process (AHP) model was used to evaluate the catchment areas of the 26 existing hospitals within the study area. Thus, with effective data collection in the form of layers of information such as transportation network, population density, land use, etc. using (GIS), the authors categorised urban land in seven categories from poor to very good for the construction of hospitals. The result of analysis indicated that existing hospitals covered approximately 24% of active urban areas within a standard access time. The result can be used for policy making and healthcare planning.